Child Abuse scale elevations on the MACI as related to abuse type - Byrnes, Kirsten (The journal of forensic psychiatry & psychology, 2022)
Child maltreatment often results in the involvement of Child Protection Services and need for psychological evaluation to assist with diagnosis and treatment. As such, evaluators must understand population specific response patterns and their impact upon test interpretation. The current study aimed to evaluate whether adolescents who experienced maltreatment would significantly elevate the Child Abuse scale on the Millon Adolescent Clinical Inventory (MACI; Millon, 1993) and if elevations occurred across all abuse types or were limited to abuse with a physical impact. The study used 194 youth, 13 to 18 years old, who were referred for evaluation at a regional diagnostic and treatment center for child maltreatment, and experienced maltreatment as deemed by a clinician. The MACIs were scored utilizing Pearson’s Q-local and Q-Global services. Frequency analysis and t-tests were performed. The majority of youth (n= 135) did not have clinically significant scores on the Child Abuse scale. Youth who experienced physical (n= 158) versus non-contact (n= 36) forms of abuse had higher scores on the Child Abuse scale (M= 59.97 and M= 35.39 respectively; p< .001). The results demonstrate how the MACI contributes information to evaluations of childhood maltreatment, while highlighting the impact of abuse type on scale elevations.